2015
DOI: 10.1016/j.nicl.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MRI and cognitive function in patients with breast cancer prior to adjuvant treatment — The role of fatigue

Abstract: An increasing body of literature indicates that chemotherapy (ChT) for breast cancer (BC) is associated with adverse effects on the brain. Recent research suggests that cognitive and brain function in patients with BC may already be compromised before the start of chemotherapy. This is the first study combining neuropsychological testing, patient-reported outcomes, and multimodal magnetic resonance imaging (MRI) to examine pretreatment cognition and various aspects of brain function and structure in a large sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
130
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(148 citation statements)
references
References 37 publications
(46 reference statements)
8
130
0
7
Order By: Relevance
“…The basal ganglia are associated with a variety of functions such as motivation to action and motor activity (Stocco et al, 2010; Arsalidou et al, 2013). Recent studies on patients with chronic fatigue syndrome, multiple sclerosis, and breast cancer have shown that fatigue is associated with dysfunction of certain brain regions including basal ganglia (Menning et al, 2015; Miller et al, 2014; Hanken et al, 2014). Moreover, malignant melanoma patients treated with the inflammatory cytokine, interferon-alpha, were found to exhibit alterations in basal ganglia glucose metabolism as well as dopamine function, which were related to fatigue (Capuron et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The basal ganglia are associated with a variety of functions such as motivation to action and motor activity (Stocco et al, 2010; Arsalidou et al, 2013). Recent studies on patients with chronic fatigue syndrome, multiple sclerosis, and breast cancer have shown that fatigue is associated with dysfunction of certain brain regions including basal ganglia (Menning et al, 2015; Miller et al, 2014; Hanken et al, 2014). Moreover, malignant melanoma patients treated with the inflammatory cytokine, interferon-alpha, were found to exhibit alterations in basal ganglia glucose metabolism as well as dopamine function, which were related to fatigue (Capuron et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Only the brain metrics and cognitive tests that were significantly different between groups were examined. To reduce the number of comparisons, a composite of the significant cognitive test scores was computed using the Mahalanobis distance, which was then log transformed (Mahalanobis, 1936; Menning et al., 2015; Stouten‐Kemperman et al., 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Several cross‐sectional and longitudinal studies have demonstrated abnormalities in brain structure and function, particularly in chemotherapy‐treated patients and survivors (D'Agata et al., 2013; Deprez et al., 2014; Jung et al., 2016; Kesler & Blayney, 2015; Lepage et al., 2014; Nudelman et al., 2014; Simo et al., 2015; Stouten‐Kemperman et al., 2014). However, many patients demonstrate differences in brain structure and function prior to chemotherapy suggesting that cancer pathogenesis, surgery/anesthesia, disease burden, host‐related, and/or other factors may contribute to early brain changes (Cimprich et al., 2010; McDonald, Conroy, Ahles, West, & Saykin, 2012; Menning et al., 2015; Sato et al., 2015; Scherling, Collins, Mackenzie, Bielajew, & Smith, 2012; Scherling, Collins, Mackenzie, Lepage, et al., 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Cancer-related fatigue (CRF) is conceptualized as a complex, multidimensional experience of reduced energy and increased need for rest that is not related to activity or relieved by sleep [2]. Post-treatment fatigue has been shown to negatively affect cognitive function [3], psychological well-being [4], and physical function [5]; reduce overall health-related quality of life [6]; and possibly influence survival rates [7]. Unfortunately, CRF is also one of the most persistent consequences of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%